A systematic literature review of Technological, Pedagogical and Content Knowledge (TPACK) in mathematics education: Future challenges for educational practice and research - Kholid, Muhammad Noor; Hendriyanto, Agus; Sahara, Sani; Muhaimin, Lukman Hakim; Juandi, Dadang; Sujadi, Imam; Kuncoro, Krida Singgih; Adnan, Mazlini (Cogent education, 2023)
This systematic literature review examines the development of Technological, Pedagogical and Content Knowledge (TPACK) in mathematics education and its impact on teaching. The study analyzed 25 peer-reviewed articles published between January of 2018 and December of 2022 from the Scopus and ERIC databases to answer four research questions. The results reveal that most studies on TPACK have been conducted in Turkey, the United States, Costa Rica, and Malaysia, with both in-service and pre-service mathematics teachers as subjects. The majority of the studies focus on the use of digital technology and identify factors that hinder the development of TPACK among mathematics teachers, including lack of confidence, resistance to change, lack of institutional support, and inadequate resources. The study recommends active participation in pedagogical technology training for teachers and prospective teachers to improve mathematics teaching. Although the use of technology in teaching and learning offers many benefits, it also presents challenges that need to be addressed to effectively integrate technology into mathematics teaching and enhance the development of TPACK among mathematics teachers.